Teknologi Digital Dan Transformasi Internal Audit Terhadap Perlakuan Laporan Keuangan : Studi Literatur - Rizka Khoirotun Nisaa,; Salsabila Maulidya Supriadi Bahrim,; Irda Agustin Kustiwi, (Jurnal Mutiara Ilmu Akuntansi, 2024)
This article discusses the impact of digital technology on the transformation of internal audit and its implications for the treatment of financial reports. As technology advances, companies are adopting digital solutions to improve the efficiency and effectiveness of their internal audit processes. This transformation not only includes the use of new tools and technologies, but also changes the paradigm and methodology of internal audit work. Digital technology provides greater capabilities in collecting, analyzing and understanding data in real-time. Internal audit can leverage advanced analytics technology, artificial intelligence, and natural language processing to identify risks, detect anomalies, and provide deeper insights into a company's finances. With the adoption of digital technology, internal audit transformation can increase audit accuracy and thoroughness, reduce the risk of human error, and enable fraud identification more effectively. In addition, technology also facilitates the implementation of more proactive and adaptive risk-based audit practices, allowing internal audit to focus on the most critical areas and provide significant added value. However, this transformation also brings new challenges, including the need to develop new skills among auditors, manage information security risks, and ensure compliance with regulations related to data privacy and security. This article details effective implementation strategies, as well as providing views on how organizations can optimize the potential of digital technology to improve the quality of financial reporting treatment. Thus, this article aims to provide in-depth insight into the role of digital technology in the transformation of internal audit and its impact on the treatment of financial statements, identify the associated benefits and challenges, and provide guidance for companies wishing to adopt such technology effectively.